Genome wide linkage mapping for black point resistance in a recombinant inbred line population of Zhongmai 578 and Jimai 22 - Chen, Tiantian; Li, Lei; Liu, Dan; Tian, Yubing; Li, Lingli; Zeng, Jianq; Rasheed, Awais; Cao, Shuanghe; Xia, Xianchun; He, Zhonghu; Liu, Jindong; Zhang, Yong (Elsevier B.V., 2025)
Black point is a black discoloration of the grain embryo that reduces the grain quality and commodity grade. Identifying the underlying genetic loci can facilitate the improvement of black point resistance in wheat. Here, 262 recombinant inbred lines (RILs) from the cross of Zhongmai 578/Jimai 22 were evaluated for their black point reactions in five environments. A high-density genetic linkage map of the RIL population was constructed with the wheat 50K single nucleotide polymorphism (SNP) array. Six stable QTLs for black point resistance were detected, QBp.caas-2A, QBp.caas-2B1, QBp.caas-2B2, QBp.caas-2D, QBp.caas-3A, and QBp.caas-5B, which explained 2.1-28.8% of the phenotypic variances. The resistance alleles of QBp.caas-2B1 and QBp.caas-2B2 were contributed by Zhongmai 578 while the others were from Jimai 22. QBp.caas-2B2, QBp.caas-2D and QBp.caas-3A overlapped with previously reported loci, whereas QBp.caas-2A, QBp.caas-2B1 and QBp.caas-5B are likely to be new. Five kompetitive allele-specific PCR (KASP) markers, Kasp_2A_BP, Kasp_2B1_BP, Kasp_2B2_BP, Kasp_3A_BP, and Kasp_5B_BP, were validated in a natural population of 165 cultivars. The findings of this study provide useful QTLs and molecular markers for the improvement of black point resistance in wheat through marker-assisted breeding.